STRATEGI GURU PAI DALAM PEMBINAAN MENTAL PESERTA DIDIK MELALUI INTERNALISASI NILAI DAN PENGEMBANGAN KECERDASAN EMOSIONAL-SPIRITUAL - Yunus, Yunus; Wahyuni, Sri; Ilman, Muhammad Zidni (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study examines the concept and strategy of mental development of students at MTs Al-Muhdariyah Tokke Village, Malangke District, North Luwu Regency. The concept of mental development applied focuses on the process of internalizing moral values, by actualizing these values ​​to students. This research is a qualitative study. Research Results Students are given a deep understanding of the importance of emotional and spiritual intelligence through the appreciation of moral values. The strategies used by Islamic Religious Education (PAI) teachers in mental development include several approaches. 1) providing opportunities for students to apply the knowledge that has been taught. 2) supervision that is directive without dictating students, providing space for independence. 3) practicing and cultivating Islamic values ​​is the core of the strategy. This acculturation involves various aspects, such as moral beliefs as the foundation of character, the Qur'an and hadith as a guide to life, fiqh as a guide to practical worship, and dates (history of Islamic culture) as a means of understanding science based on Islamic history. Mental development at MTs Al-Muhdariyah Tokke Village is carried out through the internalization of moral values ​​which emphasize the importance of emotional and spiritual intelligence.